Beekeeping practice: effects of Apis mellifera virgin queen management on ovary development - Berger, Bruno [UNESP]; Poiani, Silvana Beani [UNESP]; da Cruz-Landim, Carminda [UNESP] (Springer Nature, 2016)
Newly emerged virgin queens are frequently imprisoned in cages either inside or outside of colonies before delivery to a new hive. Ovary integrity and proper functioning is the primary factor in a queen’s success as the colony mother. In this work, histological studies on ovaries are used to evaluate the effect of virgin queen imprisonment both out and inside the colony. The results show that the ovarian follicles of virgin queens maintained out of the colony advance only until the beginning of differentiation of oocytes and nurse cells, the vitellarium does not differentiate, and cell death is observed. For virgin queens caged inside a colony, oogenesis progresses until nurse cell and oocyte differentiation is completed, and the vitellarium shows initial differentiation. The results suggest that the best method for a head start of a queen’s fertility is to maintain her inside the colony until introduction into a new hive.
Keywords: apiculture; caged queen; cell death; egg production; histology